A lei 10.639 em Feira de Santana – Ba: percursos e visões do conselho municipal e das escolas na efetivação das políticas afirmativas (2003-2012) - De Araújo, Maria Santana (2018)
This Dissertation problematizes the implementation of Federal Law 10.639 / 2003 in the municipality of Feira de Santana from 2003 to 2012. It is guided by the question What are the axes or computer centers that mobilized and articulated organized collective subjects that influenced / influenced the directions of affirmative policies in the municipality of Feira de Santana, in the face of Law 10.639 / 2003, and that organic projects of ethnic relations they represented? The general objective of the research was to identify and analyze the axes of mobilization and articulation of the individuals who, in action in the period 2003-2012, influenced the design of the implementation of Law 10.639 / 2003, whether within the municipal education system or in the municipal schools of Feira de Santana. Associated with this the specific objectives were formulated in the following terms: To understand the projects defended by the members of the Municipal Council of Education with a view to the materialization of Federal Law 10.639 / 2003 and To understand the relations established in the school community and their implications in pedagogical planning, with focus on ethno-racial relations, Afro-Brazilian and African History and Culture, from 2003 to 2012. The methodology used was based on content analysis, and was based on the categories of integral State, political society and civil society of Antonio Gramsci, in addition to the concepts of ethnic-racial relations and racism. The sources that subsidized the study were written documents of the Municipal Council of Education (CME), such as minutes of meetings and proposals from this body, as well as the Political Projects Pedagogical of two municipal schools. The research showed that the CME, in articulation with the Municipal Secretariat, chose as a priority bureaucratic issues: school authorization, calendar and school regiment were the priorities of the CME, which ensured the functioning of the educational system without substantive changes in the course of the actions of the competent bodies, preserving intervention standards that indicate indifference to the Federal Law in the case of CME. The study of the Political Pedagogical Projects of the schools revealed a silencing of the Law. To have been silent in the social / racial scenario of the period may have represented a refined form of racializing pedagogical planning, excluding the debate of unequal racial relations in society and in school